Corporate Environmentalism in Malaysia: Exploring the Media’s Pressure on Businesses (Jurnal Pembangunan Sosial, 2011)
A business pertaining to the environment has three basic issues. First, in order to produce products it takes too much from the environment and does so in a harmful way; second, the product it makes require excessive amounts of energy, toxins, and pollutants; and finally, the method of manufacture and the products themselves produce extraordinary waste and cause harm to present and future generations of all species including humans. The only way out of the unsustainability of business practices is through re-engineering business activities inline with the principle of ecology. Hence, it is crucial for businesses to take a fresh look at the damages that they have done to the natural environment and their far-reaching impacts to human survival. Businesses will not do so, unless there is an increasing pressure from the stakeholders including the public and the government alike to improve their corporate environmentalism. In order to exert an influence on the industry, the media needs to be more proactive in reporting and investigating environmental issues pertaining to business activities. This paper tries to unfold the efficacy and the role of the media in Malaysia as a pressure group towards corporate environmentalism in the Malaysian businesses. This report involves a qualitative study of four major newspaper agencies in the country – two vernacular daily newspapers, one daily English newspaper and a bi-monthly newspaper. Four senior reporters involved in the face-to-face interviews. The conversations were audio-taped and then were analysed using the NVivo Version 7 software programme. This report highlights amongst other things the media challenges pertaining to environmental issues, and the media approaches to exert pressure on businesses. It also investigates the efficacy of the media to exert influence on the Malaysian industries to be more environmentally responsible and forward ways to improve media pressure against unscrupulous business activities.